2021
DOI: 10.48550/arxiv.2109.09600
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dynamical States and Bifurcations in Coupled Thermoacoustic Oscillators

Sneha Srikanth,
Samadhan A. Pawar,
Krishna Manoj
et al.

Abstract: The emergence of rich dynamical phenomena in coupled self-sustained oscillators, primarily synchronization and amplitude death, has attracted considerable interest in several fields of science and engineering. Here, we present a comprehensive theoretical study on the manifestation of these exquisite phenomena in a reduced-order model of two coupled Rijke tube oscillators, which are prototypical thermoacoustic oscillators. We characterize the dynamical behaviors of two such identical and non-identical oscillato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…This type of coupling is introduced in an experimental system by connecting the two oscillators using a coupling tube, whose diameter is smaller than the diameter of the Rijke tube 272,280 . The increase in the length (l c ) and the diameter (d) of the coupling tube in experiments have direct correspondence with an increase in the time delay (τ) and the strength of coupling (K τ ) between the oscillators in the model 262,272 . On the other hand, dissipative coupling accounts for the dissipation of energy during the transfer of information from one oscillator to another as a consequence of mutual interaction.…”
Section: A Mutual Synchronization Of Coupled Rijke Tube Oscillatorsmentioning
confidence: 71%
See 3 more Smart Citations

Rijke tube: A nonlinear oscillator

Manoj,
Pawar,
Kurths
et al. 2022
Preprint
Self Cite
“…This type of coupling is introduced in an experimental system by connecting the two oscillators using a coupling tube, whose diameter is smaller than the diameter of the Rijke tube 272,280 . The increase in the length (l c ) and the diameter (d) of the coupling tube in experiments have direct correspondence with an increase in the time delay (τ) and the strength of coupling (K τ ) between the oscillators in the model 262,272 . On the other hand, dissipative coupling accounts for the dissipation of energy during the transfer of information from one oscillator to another as a consequence of mutual interaction.…”
Section: A Mutual Synchronization Of Coupled Rijke Tube Oscillatorsmentioning
confidence: 71%
“…The introduction of coupling between two such oscillators significantly changes their dynamical properties. In this case, Srikanth et al 262,269 found a forward shift in the occurrence of Hopf bifurcation along with a reduction in the amplitude of limit cycle oscillations when compared to these properties for an isolated Rijke tube oscillator. Recently, there has been an increased interest in studying the behavior of two coupled Rijke tube oscillators 262,[270][271][272][273][274] .…”
Section: A Mutual Synchronization Of Coupled Rijke Tube Oscillatorsmentioning
confidence: 91%
See 2 more Smart Citations

Rijke tube: A nonlinear oscillator

Manoj,
Pawar,
Kurths
et al. 2022
Preprint
Self Cite
“…At appropriate coupling parameter values, coupled systems approach the same state of oscillation quenching, known as amplitude death [8]. Through experimental and numerical analysis, amplitude death and partial amplitude death have been discovered in coupled laminar thermoacoustic systems [9][10][11][12]. In addition, a few studies have investigated the dynamics of mutually coupled turbulent combustors [13][14][15][16], and have also reported the presence of amplitude death in them [14].…”
Section: Introductionmentioning
confidence: 99%